Effectiveness of Islamic Bank Earning: Paramatic Stochastic Frontier Approaches - Tuti Zakiyah maimun; Arya Samudra Mahardhika (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
: This study aimed to determine the level of Effectiveness of Islamic banks earning by the Stochastic Frontier Approach (SFA) approach and assess the effect of banking financial performance on Indonesian Islamic banks listed on IDX. The population in this studied are all sharia banking companies listed on the Indonesia Stock Exchange in the 2014-2019 period. Sampling used a purposive sampling technique and produced a sample of 60 Islamic banking companies. The data source used in this study is the annual secondary data. The results of the hypothesis are ROA has no significant effect on the effectiveness of company earnings, Finance Deposit to Ratio (FDR) is having a substantial impact on the efficacy of company earnings, Asset Quality is having a considerable effect on the effectiveness of company earnings, Effectiveness (BOPO) does not substantially affect on Earningability (ROA), Solvency Ratio (CAR) has no impact on the effectiveness of the company's earning, and Market Sensitivity (IRR) has no significant effect on earningability.